Kompetensi Teknologi-Pedagogi-Konten (TPACK) Guru Bahasa Arab di Era Digital: Meta-Sintesis - Julham Hukom (CV. SINAR HOWUHOWU, 2026)
The success of technology integration in Arabic language teaching depends not merely on device availability, but on teachers' competence in synergistically combining technological, pedagogical, and content knowledge—known as Technological Pedagogical Content Knowledge (TPACK). Although the TPACK framework has been widely studied in general education, reviews specifically synthesizing its application among Arabic language teachers remain limited. This meta-synthesis aims to integrate and interpret findings from empirical studies on Arabic language teachers' TPACK to produce a more comprehensive understanding. A systematic search was conducted across Google Scholar, Scopus, Web of Science, and ERIC for the period 2019–2025. Of 193 articles identified, 18 studies met the inclusion criteria and were analyzed using Noblit and Hare's (1988) meta-ethnographic approach. Analysis yielded four synthetic themes: (1) the TPACK profile of Arabic language teachers which still needs improvement, particularly in TK and integrated TPACK components; (2) contextual factors shaping TPACK, including teaching experience, self-confidence, and institutional support; (3) the COVID-19 pandemic as an accelerator and test of teachers' TPACK; and (4) effective TPACK development strategies through practice-based training and professional learning communities. This meta-synthesis contributes a contextual TPACK framework for Arabic language teachers and formulates implications for teacher education and school policy.